The Full-Length Transcriptome Provides New Insights Into the Transcript Complexity of Abdominal Adipose and Subcutaneous Adipose in Pekin Ducks - Sun, Dandan; Li, Xiaoqin; Yin, Zhongtao; Hou, Zhuocheng (Frontiers in Physiology, 2021)
Adipose tissues have a central role in organisms, and adipose content is a crucial economic trait of poultry. Pekin duck is an ideal model to study the mechanism of abdominal and subcutaneous adipose deposition for its high ability of adipose synthesis and deposition. However, there has been no systematic analysis of the dynamics of differential alternative splicing of abdominal and subcutaneous adipose in Pekin duck. In our study, the PacBio Iso-Seq technology was applied to explore the transcriptional complexity of abdominal and subcutaneous adipose in Pekin ducks. In total, 143,931 and 111,337 full-length non-chimeric transcriptome sequences of abdominal and subcutaneous adipocytes were obtained from 41.78GB raw data, respectively. These data led us to identify 19,212 lncRNAs and 74,571 alternative splicing events. In addition, combined with the next-generation sequencing technology, we correlated the structure and function annotation with the differential expression profiles of abdominal and subcutaneous adipose transcripts. This study identified lots of novel alternative splicing events and major transcripts of transcription factors related to adipose synthesis. STAT3 was reported as a vital gene for adipogenesis, and we found that its major transcript is STAT3-1, which may play a considerable role in the process of adipose synthesis in Pekin duck. This study greatly increases our understanding of the gene models, genome annotations, genome structures, and the complexity and diversity of abdominal and subcutaneous adipose in Pekin duck. These data provide insights into the regulation of alternative splicing events, which form an essential part of transcript diversity during adipogenesis in poultry.